TASS upolnomochen zaiavit' 3-4 . TASS Is Authorized to Declare…part 3, 4 - Fokin, Vladimir (Gosteleradio SSSR, 1984)
Continuation of a political detective story. A spy is sent to Moscow. Soviet intelligence is trying to neutralize him and thus prevent a revolt, prepared by the CIA, in the fictional third-world state of Nagonia.